BS EN 4013. Aerospace series. Shank nuts, self-locking, in heat resisting nickel base alloy NI-PH2601 (Inconel 718), silver plated. Classification. 1 550 MPa (at ambient temperature) / 600 °C. (26th January 2023) - British Standards Institution,
No abstract available